2013
DOI: 10.1111/php.12189
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Light‐Emitting Diode (LED) Therapy at Wavelengths of 635 and 945 nm on Bothrops moojeni Venom‐Induced Hyperalgesia

Abstract: Envenoming induced by Bothrops snakes is characterized by drastic local tissue damage involving hemorrhage, myonecrosis and proeminent inflammatory and hyperalgesic response. The most effective treatment is antivenom therapy, which is ineffective in neutralizing the local response. Herein, it was evaluated the effectiveness of light-emitting diode (LED) at wavelengths of 635 and 945 nm in reducing inflammatory hyperalgesia induced by Bothrops moojeni venom (BmV) in mice, produced by an subplantar injection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Herein, the intraplantar injection of Bmv induced mechanical allodynia and hyperalgesia. These results are in accordance with previous data demonstrating that Bmv induces potent mechanical allodynia and hyperalgesia in mice [ 24 , 30 ]. Photobiomodulation applied 30 min and 3 h after Bmv reversed both mechanical allodynia and hyperalgesia.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Herein, the intraplantar injection of Bmv induced mechanical allodynia and hyperalgesia. These results are in accordance with previous data demonstrating that Bmv induces potent mechanical allodynia and hyperalgesia in mice [ 24 , 30 ]. Photobiomodulation applied 30 min and 3 h after Bmv reversed both mechanical allodynia and hyperalgesia.…”
Section: Discussionsupporting
confidence: 94%
“…From these data, we confirmed that photobiomodulation, in fact, is effective in reducing Bmv-induced local pain. In our study, as in previous studies [ 24 , 30 ], we observed that antinociception was not related to AV treatment, since it was not able to interfere with mechanical sensitivity of mice. Also, the association of LLLT and AV did not modify the effect of LLLT alone, reinforcing the therapeutic potential of LLL in treating local effects induced by bothrops venoms.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…snake venoms (see review by Silva et al, 2018 [ 209 ]). These studies have demonstrated that these therapies, when applied after venom injection in animals, reduced venom-induced local effects such as edema [ 210 , 211 ], hyperalgesia [ 211 , 212 ], hemorrhage [ 213 ], and myonecrosis [ 211 , 214 , 215 ].…”
Section: The Potential Of Photobiomodulation Therapy For Snakebite Envenomingmentioning
confidence: 99%
“…This proposal is based on the literature that shows a reduction of the local effects induced by various Bothrops snake venoms after photobiostimulation such as myonecrosis , 18,19 inflammation, [20][21][22] hemorrhage 22 and pain. 21,23 Moreover, Barbosa et al (2010) 24 reported that LLL treatment significantly reduced the muscle edema, leukocyte influx and myonecrosis induced by BthTX-I or -II isolated from B. jararacussu snake venom.…”
Section: Introductionmentioning
confidence: 99%